1990
DOI: 10.3168/jds.s0022-0302(90)78964-3
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Pattern of Staphylococcus aureus from Bovine Intramammary Infections

Abstract: Twenty-one quarters of seven cows were experimentally infected with Staphylococcus aureus (ATCC 29740) to study the shedding pattern in quarter milk samples. Of 991 consecutive quarter milk samples collected from infected quarters during the trial, 745 were positive for S. aureus by bacteriological culture. The sensitivity of a single quarter milk sample to determine infection status of a quarter was 74.5% based on the mean of each gland's recovery pattern. Sensitivity of bacterial culture increased to 94% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
193
2
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(206 citation statements)
references
References 2 publications
2
193
2
9
Order By: Relevance
“…The determination of the IMI based on a single result is most of the time not very accurate [37]. Some chronically infected quarters eliminate bacteria in milk sporadically, leading to possible false negative results [7,29,43]. Taking repeated samples limits the number of false-negative samples.…”
Section: Figure 8 Geometric Mean Scc (᭜) and Its 95% CI (-) Of Quartmentioning
confidence: 99%
“…The determination of the IMI based on a single result is most of the time not very accurate [37]. Some chronically infected quarters eliminate bacteria in milk sporadically, leading to possible false negative results [7,29,43]. Taking repeated samples limits the number of false-negative samples.…”
Section: Figure 8 Geometric Mean Scc (᭜) and Its 95% CI (-) Of Quartmentioning
confidence: 99%
“…Nevertheless, if a pathogen was recovered only in one pair of the duplicate, the quarter was considered as non-infected according to the microbiological results and was considered to display non--significant growth, except in the case of S. aureus or Streptococcus agalactiae infection. This exception was applied for S. agalactiae because it is regarded as a highly contagious obligate parasite of the bovine mammary gland (Keefe 1997) and for S. aureus due to its peculiar shedding pattern, particularly because the shedding pattern could be below the detection limit of the microbiological method employed (Sears et al 1990, Zecconi et al 1997, Godden et al 2002, Walker et al 2010. (B) Second, the milk sample was regarded as microbiologically positive if at least one of the duplicate samples (single S1 or S2) was microbiologically positive regardless of which mastitis pathogen was isolated.…”
Section: Methodsmentioning
confidence: 99%
“…Although some investigators have used inoculums of 0.01 ml, others have increased inoculum volumes to 0.05-0.1 ml, thereby increasing the sensitivity of microbiologic screening. 4,8,9 Other investigators have reported variable inoculums within a single study using 0.1 and 0.05, 13 or 0.01-0.03 ml. 10 Considering the daily samples, although statistically significant, there was only a 2% difference in the sensitivity of culture using the larger inoculum.…”
Section: Introductionmentioning
confidence: 99%
“…Milk samples from S. aureus-positive quarters that were culture positive using 0.01 ml were unavailable for reculture using 0.1 ml and were considered positive at the larger inoculum for the analysis. Sensitivities and specificities of a single microbiologic culture in identifying S. aureus IMI and the comparison of the ability to detect a S. aureus IMI between the 2 inoculum volumes were calculated considering each quarter sample independently 13 (roctab, roccomp, STATA v. 11) b applying the definition of a S. aureus-positive quarter (at least 2 of the first 3 consecutive samples culture positive with $1 CFU of S. aureus/0.1 ml) and assuming a disease-free status in quarters defined as S. aureus negative. Quarters with no history of S. aureus, but repeatedly testing positive for S. aureus at some point after the third sample, were considered new infections and not included in the analysis (n 5 3).…”
Section: Introductionmentioning
confidence: 99%